An American language : the history of Spanish in the United States - Lozano, Rosina, 1978- (American crossroads, 2018)
"An American Language is a tour de force that revolutionizes our understanding of U.S. history. It reveals the origins of Spanish as a language binding residents of the Southwest to the politics and culture of an expanding nation in the 1840s. As the West increasingly integrated into the United States over the following century, struggles over power, identity, and citizenship transformed the place of the Spanish language in the nation. An American Language is a history that reimagines what it means to be an American--with profound implications for our own time"--Provided by publisher.